2014
DOI: 10.4103/0972-124x.131329
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of nanocrystalline hydroxyapatite and synthetic resorbable hydroxyapatite graft in the treatment of intrabony defects: A clinical and radiographic study

Abstract: Background:The aim of this study is to compare, clinically and radiographically, the effectiveness of nanocrystalline hydroxyapatite (NHA) and synthetic resorbable hydroxyapatite (HA) in the treatment of intrabony defects.Materials and Methods:Ten subjects with bilateral defects, with probing depth (PD) 6-9 mm and radiographic evidence of an intraosseous component ≥4 mm participated in the present study. Subjects were allocated randomly to treatment with NHA (test group) or HA (control group). At baseline, 3 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Except for one study, which used a parallel study design [ 52 ], each experiment used a split-mouth design. Five out of seven studies used synthetic BGs [ 52 , 53 , 54 , 55 , 56 ], whereas one study used autogenous BG [ 57 ] and another study used xenogenic graft [ 58 ]. The maximum follow-up time varied among the included trials, ranging from 6 months in five trials to 9 and 12 months in the other two, respectively [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Except for one study, which used a parallel study design [ 52 ], each experiment used a split-mouth design. Five out of seven studies used synthetic BGs [ 52 , 53 , 54 , 55 , 56 ], whereas one study used autogenous BG [ 57 ] and another study used xenogenic graft [ 58 ]. The maximum follow-up time varied among the included trials, ranging from 6 months in five trials to 9 and 12 months in the other two, respectively [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…The maximum follow-up time varied among the included trials, ranging from 6 months in five trials to 9 and 12 months in the other two, respectively [ 52 ]. Four studies reported using post-operative antibiotics [ 52 , 55 , 57 , 58 ], whereas three studies did not disclose the use of post-operative antibiotics [ 53 , 54 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone substitutes in the form of Nano hydroxyapatite can be used successfully to fill osseous defect as it has advantages like close contact with surrounding tissues, quick resorption characteristics and large number of molecules on the surface (16) .…”
Section: Discussionmentioning
confidence: 99%
“…Bansal et al revealed the application of n-HA can improve clinical and radiographic parameters in the treatment of periodontal intrabony defect [50]. Elgendy et al compared clinical and radiographic outcomes of nanocrystalline hydroxyapatite with or without PRF membranes in the treatment of periodontal intrabony defects and concluded n-HA is a suitable bone substitute in the periodontal treatment of intrabony defect.…”
Section: The Usage Of N-ha In Human Periodontal Intrabony Defectsmentioning
confidence: 99%